(3TQM gOGjI GdMceIs - (3GdejHPj, , bGVj ejQ, bGVj ejQ, MSjf Hf eYjf GdOjf, GdejHPj, J (B910(3g` (B1504(3es ((3fLe GdOjf Hf eMeOs)
(3ChdgG (B:s
(3ChdgG(B: (3GdgOGjI CeQ ef dOjg, Cj fGT ef YfOg CeG HhGSWI Ch HOhfgG ShGA cGf HeYfi GdOdGdI Ydi eG jhUd Edi GdeWdhHs
(3BNQgG (B:s
(3BNQgG(B: (3Ef GdKGHJ HGdHQgGf GeJfGY UOhQ JMQjaGJ ZjQ eJfGgjI ef GdbhI GdLSeGfjI eWdbG ShGA CcGf HhGSWI Ch HOhfgG hdjS ajg HGdNUI HGdJGdj adG jchf GdLhGH gPG UMjMG CjVGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 260s
(3cTa GdXfhf, L (B2: 2029s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs